Swipe, Click, Abandon? Investigating University Students’ Engagement with Lifestyle Management Apps - Sobia Arshad; Iftikhar Alam Khan; Mary Gella; Danish Ali; Akifa Abbas (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Purpose: This study examines university students’ use and retention of well-being apps, focusing on mental and physical health. While these apps aim to enhance productivity, health, and well-being, many students either abandon them or avoid them altogether. This research explores the key factors influencing adoption, usage trends, and reasons for discontinuation, aiming to provide valuable insights for app developers and researchers in the field. Methodology: The study used a mixed-methods approach, integrating qualitative insights with quantitative survey data. In an online survey, 105 undergraduates answered questions on their preferences, engagement barriers, selection criteria, and use of lifestyle management apps. While open-ended questions allowed for the exploration of individual motives and difficulties, descriptive statistics were employed to identify behaviors. Findings: Many students express interest in well-being apps, yet a large proportion either never use them or stop due to usability issues, lack of personalized options, or preference for traditional methods. Fitness and wellness apps are the most popular, while financial management and habit-building apps receive less engagement. Key reasons for abandonment include perceived ineffectiveness, forgetting to use them, and paywalls or excessive ads. Novelty: This study offers a more focused knowledge of user behavior in this demographic by concentrating exclusively on lifestyle management apps among university students, in contrast to earlier research that looks at mobile app engagement more widely. Implications: To improve retention, findings indicate that developers should give priority to tailored experiences, intuitive design, and long-term engagement tactics. Furthermore, addressing obstacles like notifications and paywalls may increase adoption rates. In order to better meet the needs of students, these insights can direct future app development.